30 years of IJSE : festschrift in honour of Professor John O'Brien. - O'Brien, J. C. (John Conway); Pettman, B. O. (International journal of social economics, 2005)
In celebration of Professor John O'Brien's considerable impact on the discipline of Social Economics, this festival of writing celebrates his unique style by producing a number of learned and substantial articles covering a very wide area within the subject area.